DEVELOPING ORGANIZATIONAL CITIZENSHIP BEHAVIOR THROUGH JOB SATISFACTION BY IMPROVING MOTIVATION AND WORK ENVIRONMENT - Nilasari, Ratna Putri; Santoso, Risa; Karnawati, Tin Agustina (LP2M Institut Teknologi dan Bisnis Asia Malang, 2023)
This study aims to determine the influence of motivation and work environment on Organizational Citizenship Behavior (OCB) with job satisfaction as an intervening variable for non-lecturer employees at ITB Asia Malang. The population of this study includes all non-lecturer employees at the ITB Asia Malang. and the sample used is 70 respondents using the saturated sample method. The result of this study (1) motivation does not significantly affect job satisfaction, (2) work environment effect the job satisfaction positively and significantly, (3) job satisfaction and motivation effect OCB positively and significantly, (4) work environment does not significantly affect OCB, (5) job satisfaction is able to mediate work environment to OCB, (6) job satisfaction is not able to mediate motivation to OCB. ITB Asia Malang needs upgrading facilities, create KPI standards for each division, systems and environments that can shape work patterns for education personnel, and maximizing roles from the division coordinator for monitoring.